Crystal structure of catena-poly-[(1-cyclopropyl-6-fluoro-4-oxo-7-(piperazin-1-ium-1-yl)-1,4-dihydroquinoline-3-carboxylate-κ2O,O′)-(μ2-4,4′-sulfonyldibenzoato-κ4O,O′:O′′,O′′′)zinc(II)] hemihydrate, C31H27ZnFN3O9.5S - Fan Zhuo-Wen (Zeitschrift für Kristallographie - New Crystal Structures, 2016)
C31H27ZnFN3O9.5S, triclinic, P1̅ (no. 2), a = 10.6434(4) Å, b = 12.6191(4) Å, c = 12.8532(5) Å, α = 93.998(3)°, β = 109.121(3)°, γ = 112.773(3)°, V = 1465.16(9) Å3, Z = 2, Rgt(F) = 0.0354, wRref(F2) = 0.1012, T = 293 K.